Evaluasi Penggunaan Aplikasi Ninja Driver di Ninja Xpress Jasinga Bogor Menggunakan PIECES Framework - Awaliyah, Rita; Rusmanto; Wibowo, Edi (LPPM STT Terpadu Nurul Fikri, 2025)
The growth of e-commerce in Indonesia has driven the need for fast and ef icient delivery services, including Ninja Xpress,which utilizes the Ninja Driver application to support courier operations. This study aims to evaluate the Ninja Driverapplication at Ninja Xpress Jasinga using the PIECES framework (Performance, Information, Control, Ef iciency, Service).The research employed a quantitative approach through questionnaires distributed to 27 couriers as respondents,complemented by interviews with the company to validate the findings. The results showed average scores for Performance(2.74), Information (3.15), Control (3.27), Ef iciency (3.10), and Service (3.07), with all aspects rated as